ISLAMIC EDUCATION AND THE EMANCIPATION OF DISABLED INDIVIDUALS - Raus, Norakyairee Mohd (Al Ulya: Jurnal Pendidikan Islam, 2022)
In this study, emancipation refers to the release of the paradigm or the provision of equal (fair) rights to the disabled individual (Orang Kurang Upaya) community based on an appreciation of the reality of disability. In contemporary social studies, the "emancipation" paradigm is essential, particularly when discussing social minority societies such as the handicapped. This is due to the fact that the disabled have been excluded from the flow of national progress in terms of education, employment, health, transportation, politics, etc. for a very long period. This study's primary purpose is to evaluate the idea of disability according to the Quran, as well as the right strategy to addressing the concerns and challenges of religiously impaired individuals. This is a qualitative research that collects data and information through document analysis. The results of a search for https://sigir.uitm.edu.my/svsi/sumberutama.php a number of the Quranic verses utilize phrases that are strongly associated with the group of handicapped people, such as deaf, stupid, blind, lame, and feeble. Some of these expressions plainly pertain to the law of rukhsah (leniency) for jihad and enforcing the demands of Sharia, while others are employed as parables to teach the nature of faith and unbelief as well as the repercussions of refusing to adopt Islam.